Morfologi Bahasa Melayu - Nazir, Faridah; Juhari, Amir; Harun, Mohd Asri; Hamid, Zanariah; Tahir, Maria (MK e-Solutions Sdn.Bhd., 2024)
This book is about grammar in the Malay language which refers to rules or systems used in oral or written form. Therefore, to deepen the linguistic field of the Malay language, it is important to understand more clearly the field of grammar study, which is the field of morphology. Morphology is a field of linguistics that studies the structure, form, and classification of words. Word structure means arranging speech sounds or symbols that become a meaningful grammatical unit. The form of a word is the appearance of a grammatical unit, whether it is a single form or the result of the process of adding, pluralizing, and doubling. Word classification is the process of classifying words based on the similarity of form and functional background with other members of the same group. ​